Skor APRI pada subyek penyakit ginjal stadium 5 hemodialisis dengan hepatitis B dan hepatitis C - Jarut, Maria E.; Moeis, Emma Sy.; Waleleng, Bradley J. (Universitas Sam Ratulangi, 2016)
Abstract: Chronic kidney disease (CKD) is a process with various etiology, resulting in a progressive descent in kidney function and generally end up with kidney failure that requires renal replacement therapy. One of the renal replacement therapy is hemodialysis. Subjects undergoing hemodialysis belong to the high-risk group for hepatitis B and hepatitis C. This study aimed to obtain the APRI scores in subjects CKD 5 HD with hepatitis B and hepatitis C. This was a retrospective observational descriptive study. This study was conducted from October to December 2014 in the medical record of Hemodialysis Unit Prof. Dr. R. D. Kandou Hospital Manado. The results showed that there were 64 subjects who met the inclusion criteria, consisted of 29 (45%) subjects with CKD 5 HD and hepatitis B and 35 (55%) subjects with CKD 5 HD and hepatitis C. Among subjects of CKD 5 HD with hepatitis B, there were 24 (37.50%) males and 5 (7.81%) females. Among subjects with CKD 5 HD and hepatitis C, there were 15 (23.43%) males and 20 (31.25%) females. Age range in subjects with CKD 5 HD and hepatitis B was 37-69 years, while in subjects with CKD 5 HD and hepatitis C was 33-65 years. The SGOT of the CKD 5 HD subjects with hepatitis B was 14-58 U/L while of the CKD 5 HD subjects with hepatitis C was 21-38 U/L. The platelet count in subjects with CKD 5 HD and hepatitis B was 78.103 /mm3 – 357.103/ mm3 while in CKD 5 HD subjects with hepatitis C was 54.103/mm3 – 417.103/mm3. Based on the SGOT and the platelet count, the final APRI scores for subjects with CKD 5 HD and hepatitis B was 0.004- 0.056 while the of CKD 5 HD subjects with hepatitis C was 0.005-0.177. The APRI scores in subjects with CKD 5 HD and hepatitis B and CKD 5 HD subjects with hepatitis C was < 0.5 which meant there was no fibrosis of the liver or fibrosis without septa. Conclusion: APRI scores were not significant to the degree of fibrosis in the early stages of either hepatitis B or hepatitis C. Keywords: CKD 5 HD, hepatitis B, hepatitis C, APRI score Abstrak: Penyakit ginjal kronik adalah suatu proses dengan etiologi beragam, mengakibatkan penurunan fungsi ginjal yang progresif dan umumnya berakhir dengan gagal ginjal yang memerlukan terapi pengganti ginjal. Salah satu terapi pengganti ginjal yaitu hemodialisis. Subyek yang menjalani hemodialisis merupakan kelompok risiko tinggi untuk virus hepatitis B dan hepatitis C. Penelitian ini bertujuan untuk mengetahui skor APRI pada subyek PGK 5 HD dengan hepatitis B dan hepatitis C. Jenis penelitian ini ialah observasional dengan rancangan deskriptif retrospektif. Penelitian ini dilaksanakan mulai Oktober sampai Desember 2014 di Bagian rekam medik Ilmu Penyakit Dalam Unit Hemodialisis RSUP Prof Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan dari 64 subyek yang memenuhi kriteria inklusi terdapat 29 (45%) subyek PGK 5 HD dengan hepatitis B dan 35 (55%) subyek PGK 5 HD dengan hepatitis C. Pada subyek PGK stadium 5 HD dengan hepatitis B, terdapat 24 laki-laki (37,50%) dan 5 perempuan (7,81%). Pada subyek PGK 5 HD dengan hepatitis C, terdapat 15 laki-laki (23,43%) dan 20 perempuan (31,25%). Rentang umur pada subyek PGK 5 HD dengan hepatitis B 37-69 tahun sedangkan rentang umur pada subyek PGK 5 HD dengan hepatitis C 33-65 tahun. Nilai SGOT subyek PGK 5 HD dengan hepatitis B 14-58 U/L sedangkan subyek PGK 5 HD dengan hepatitis C 21-38 U/L. Jumlah trombosit pada subyek PGK 5 HD dengan hepatitis B 78.103/mm3– 357.103/mm3sedangkan subyek PGK 5 HD dengan hepatitis C 54.103/mm3– 417.103/mm3. Berdasarkan nilai SGOT dan jumlah trombosit yang diperoleh maka hasil perhitungan skor APRI untuk subyek PGK 5 HD dengan hepatitis B 0,004-0,056 sedangkan pada subyek PGK 5 HD dengan hepatitis C 0,005-0,177. Skor APRI pada subyek PGK 5 HD dengan hepatitis B dan subyek PGK 5 HD dengan hepatitis C <0,5, yang menunjukkan tidak terdapat fibrosis pada hati atau terdapat fibrosis tanpa septa. Simpulan: Skor APRI tidak bermakna terhadap derajat fibrosis stadium awal baik pada hepatitis B ataupun heptitis C.Kata kunci: PGK 5 HD, hepatitis B, hepatitis C, skor APRI